(untitled) (Raparin Journal of Humanities (RJH), 2021)
The research aims at identifying (The effectiveness of an educational program based on theory of cognitive load in the development of reasoning among students in the eighth grade in the social material). Through the application of the reasoning Test, which was prepared by (Al-Jabari, 1994) for Basic school students and applied to the Iraqi environment, the standard measure is (50) paragraphs for measuring reasoning, and the researcher has followed descriptive and experimental approaches. The study participants were (74) male and female students randomly divided into two groups: Experimental Group (37), male and female students and a group of control (37), male and female students. The researcher taught the experimental group using the educational program based on the cognitive load theory, while the control group was taught by traditional education. The results of the study showed that the students of the experimental group who studied according to the educational program are superior to the students of the control group who studied in the traditional method of reasoning. The results also showed that there are no differences between the average grades of the test for males and females in the test of reasoning. The students of the experimental group who studied social studies according to the educational program based on the cognitive load theory.